GREEN FISCAL POLICY IN MOLDOVA: ALIGNMENT WITH THE EUROPEAN UNION STANDARDS FOR SUSTAINABLE TRANSITION - Chironachi, Corina; Clichici, Dorina (Economy and Sociology, 2025)
Moldova has been a candidate country for European Union (EU) membership since 2022. With this status came the commitment to align its national policies with European standards. This article analyses the current state of green fiscal policy, the actions needed to meet EU requirements, and highlights its role in the green transition and sustainable development. The methodology used includes both a comparative analysis of the legal framework and a quantitative analysis of green tax revenues between 2018 and 2024, the data being selected from the Eurostat and the Ministry of Finance of Moldova databases. The results suggest that fiscal policies are not yet fully integrated into a coherent strategy for financing the green transition. However, progress has been made towards building an environmental taxation system. Several obstacles have been identified. These include the lack of a comprehensive carbon-pricing system, underfunding of green projects, and structural and administrative barriers. This article is relevant due to the main gaps and opportunities for fiscal alignment that have been identified. It was emphasised that the establishment of a carbon pricing system, climate budget tagging (CBT), and extended producer responsibility (EPR) schemes is necessary. The paper provides insights for policy decisions, helping to transform green fiscal policy from a mere revenue-raising tool into an engine for Moldova’s sustainable transition.